Diflunisal and its conjugates in patients with renal failure. - Dickinson, R G (1991)
Six patients with renal failure were given a single oral dose (250 mg) of diflunisal. In contrast to the acyl glucuronide, the phenolic glucuronide and sulphate conjugates showed the capacity to accumulate in plasma, suggesting that systemic instability of the acyl glucuronide contributes, via hydrolysis, to plasma concentrations of diflunisal itself. Although earlier studies in renal failure patients have almost certainly underestimated diflunisal clearance (by overestimation of plasma diflunisal concentrations through unrecognized acidic hydrolysis of diflunisal sulphate during analysis), the present results suggest that the reported decrease in clearance was not attributable only to this analytical artifact.